Variability of the microbiota in traditional Caciocavallo, Scamorza and Caciotta cheeses manufactured with raw milk and natural cultures. (26th May 2021) - Del Matto, Ilaria; Rossi, Franca; Iannitto, Giorgio; Petrone, Domenico; Mastrodomenico, Maria Teresa; Alessiani, Alessandra; Sacchini, Lorena; Amadoro, Carmela; Tucci, Patrizia; Marino, Lucio
Abstract : Numerical and taxonomical variability of dominant microbial groups was investigated for 52 lots of traditional raw milk cheeses Caciocavallo, Scamorza and Caciotta from two dairy manufacturers. Microorganisms were characterised by 16S rRNA gene sequencing and detection of specific genes. Different lactic acid bacteria (LAB) growth dynamics between dairies, switches in the predominant LAB species and lot‐specific presence of certain bacterial groups were observed. The presence of virulence genes in enterococcal isolates, the presence of a tyrosine decarboxylase ( tdcA ) gene in a Lacticaseibacillus paracasei isolate and water activity ( a w ) and pH permissive for pathogen growth indicated the need for interventions that stabilise the microbiota. Abstract : Distinctness of microbiota dynamics and composition in traditional cheeses according to production lot and manufacturer.